The Relationship of Emotional Intelligence and Self-Efficacy with Academic Procrastination in Student - Reny Khaerany Nisfary; Wiwik Sulistyaningsih; Irna Minauli; Triana Hermawati (Al Hikmah: Journal of Education, 2023)
Academic procrastination carried out in various fields is often the cause of the failure of a teenager/student. Procrastination has many negative impacts, in the form of delays, wasted time, tasks become neglected, even when completed the results are not optimal. This research was conducted to examine the relationship between emotional intelligence and self-efficacy with academic procrastination in junior high school (SMP) students. This study used an explanatory method, with a population of 159 students andÂ  a sample of 25% in the study, namely 40 students at the SMP Muhammadiyah 3 Medan, the data collection method used was a Likert scale to measure the independent variables, namely emotional intelligence and self-efficacy by the dependent variable is academic procrastination. Then, research instruments were tested in the form of validity and reliability tests, while the data analysis techniques used were correlation techniques, simple and multiple linear regression, and partial correlation. The results showed that the average student was in the category of academic procrastination, moderate emotional intelligence and self-efficacy, and in the regression there was a significant and negative effect between emotional intelligence and self-efficacy on academic procrastination, thus partially emotional intelligence and efficacy were significantly can predict academic procrastination, emotional intelligence is higher than self-efficacy in reducing academic procrastination attitudes. simple and multiple linear regression, and partial correlation. The results of this study are expected to contribute to schools or educators in order to reduce students' academic procrastination rates by facilitating teaching and learning that fosters emotional intelligence and increases students' self-confidence to carry out mandated tasks